Sustainability improvement of public toilets at Teluk Kemang, Malaysia - Kobalu, Rajendran (2018)
It is important to maintain public hygiene and sanitation by providing clean public toilets with sufficient water supply in public and tourist spot. Hence, this study is carried out to investigates patrons’ expectations and perceptions of service quality in public toilet facilities provided and measures their “satisfaction gap.” A total of 599 patrons were involved in this study which was carried out in Teluk Kemang beaches along Port Dickson coastline, Strait of Malacca (Malaysia). A modified SERVQUAL 26-item instrument was used to assess patrons’ expectations before and their perceptions after using public toilets facilities provided in the area. SERVQUAL is made up of five dimensions which are Tangibles, Reliability, Responsiveness, Assurance and Empathy. The present study utilised standardised self-completion questionnaire where convenience sampling method was utilised. The “satisfaction gap” was then measured. The results showed that monthly income, gender, age group and educational level were significantly associated (p<0.05) with overall satisfaction of the respondents. There was a significant difference between the satisfactions towards service provided (p < 0.001) with regard to all of the SERVQUAL dimensions. The most significant factors of service quality were gender, monthly income, responsiveness, reliability, tangible and assurance. In conclusion, service providers should give emphasis to the patron’s individual attention and emotional aspects of care since this dimension are very important in measuring service quality.